Perancangan Standar Operasional Prosedur (SOP) Pengelolaan Dana Bantuan Operasional Penyelenggaraan (BOP) pada Raudhatul Athfal - Aprilia, Fadia Julfa; Ulupui , I Gusti Ketut Agung; Nindito, Marsellisa (LPPM Universitas Negeri Jakarta, 2025)
This study aims to design a Standard Operating Procedure (SOP) for the management of Operational Assistance Funds (BOP) at Raudhatul Athfal (RA) Al Jabbaar. The research addresses issues related to the planning, submission, utilization, and financial accountability of BOP funds that are often not aligned with the technical guidelines due to limited understanding. Using a qualitative descriptive method and the ADDIE development model (limited to the stages of Analysis, Design, and Development), data were collected through interviews and direct observation involving the school principal and treasurer. The study produced four SOP flowcharts related to the planning (RKARA), submission, management, and accountability of BOP funds. These SOPs are expected to improve efficiency, effectiveness, and compliance with regulations at RA Al Jabbaar.